Atypical fibroxanthoma and pleomorphic dermal sarcoma: A reappraisal. (28th July 2020) - Cesinaro, Anna Maria; Gallo, Graziana; Tramontozzi, Sabrina; Migaldi, Mario
Abstract: Background: Atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) share clinical, pathological, immunohistochemical and molecular features, though PDS is associated with a more aggressive behavior. Methods: We reviewed 71 tumors fulfilling criteria for AFX and PDS to further stratify their biological potential. Results: Lesions were mainly located on the scalps of elderly men, and were often ulcerated. One case was necrotic, one showed vascular invasion, and one showed perineural invasion. Fifty‐one tumors were limited to reticular dermis (71.8%), 20 invaded subcutaneous tissue, focally in 13 cases (18.3%), and diffusely in seven (9.9%). Subcutaneous invasion was present significantly more often in tumors showing predominantly spindle compared to pleomorphic/mixed cell morphology ( P = 0.02). At a follow‐up of 17‐125 months, 4 cases recurred locally, 4, 6, 10 and 13 months after surgery; no metastases were observed. Three tumors were composed of spindle cells, and one of clear cells. Three cases had margins focally involved, while the fourth case had clear margins. Conclusion: Depth of invasion and state of margins are criteria predicting prognosis in AFX/PDS; in addition, spindle cell morphology seems to be related to a more infiltrative pattern of growth and to aggressiveness. Grouping these tumors on a morphologic base could help to clarify their different biological behavior.